Robin Hood math : take control of the algorithms that run your life - Giansiracusa, Noah (Riverhead Books, 2025)
"Award-winning mathematician Noah Giansiracusa explains how the rich and powerful use formulas to get ahead-and how the rest of us can use these same formulas in our everyday lives to make better decisions, act in our own best interests, and thrive"--